STRATEGI HNI-HPAI (HALAL NETWORK INTERNASIONAL-HERBA PENAWAR ALWAHIDA INDONESIA) DALAM MEMBERDAYAKAN EKONOMI KELUARGA - ruslaini - (Jurnal Ilmiah Ekonomi Islam, 2023)
PT Halal Network International Herba Penawar Alwahida Indonesia, known as HNI-HPAI is one of the Halal Network Business companies based in Indonesia. The company's vision is to become the main reference for the most qualified halal products supported by the application of the latest technology in Customer Relationship Management (CRM). This research is a field research with the data sources were gathered from primary and secondary data, while the data collection techniques were carried out through in-depth interview techniques with research subjects, observation and documentation by conducting a review on various references in relevance to the research focus. The results obtained from this research showed that the HNI-HPAI empowerment strategies have been focusing on two sectors; empowerment on family health and empowerment on family economy. The strategies of HNI-HPAI in empowering family health have been done in accordance with the basic concept of thibbun Nabawi, that is imitating prophet Muhammad saw's lifestyle and daily diet patterns that are synergized with local wisdom, in this case the traditional herbal consumption easily found in this country. While the empowerment strategies on family economy have been done by adopting the concept of Hijrah Lifestyle, that is the migration consumption to products of HNI, which becomes the axis of enthusiasm for business activities as well as the basis for creating a more profound and fundamental creativity, and all of those activities are built from home (All start from Home).